Personalised learning in higher education for health sciences: a scoping review - Majid Ali; Izyan A. Wahab; Hasniza Zaman Huri; Muhamad Saiful Yusoff (BMC Medical Education)
Abstract Background Personalised learning approaches have gained increasing attention in higher education, particularly in health sciences, due to their potential to enhance student engagement and learning outcomes. However, the implementation and effectiveness of personalised learning strategies in health professions higher education remain unclear. This scoping review aims to map the existing literature on personalised learning in health sciences higher education, identifying key concepts, gaps in knowledge, and areas for future research. Methods We conducted a comprehensive search of five electronic databases: PubMed, Scopus, Google Scholar, Educational Research Complete, and JSTOR. The search strategy employed various combinations of keywords related to personalised learning and health sciences higher education. Studies published in English between 2000 and 2024 were included. Two independent reviewers screened titles, abstracts, and full texts. Data were extracted using a data extraction form. The review followed the methodological framework outlined by Arksey and O’Malley and adhered to the PRISMA-ScR guidelines. Results The initial search yielded 1,247 records, with another 15 identified through other sources. After removing duplicates, 583 records were screened, resulting in 42 full-text articles assessed for eligibility. Ultimately, 11 studies met the inclusion criteria and were included in the qualitative synthesis. The review identified various personalised learning approaches implemented across different health science disciplines, including medicine, nursing, pharmacy, and dentistry. Key themes emerged around adaptive learning technologies, individualised feedback mechanisms, and student-centred curriculum design. Challenges in the implementation and assessment of personalised learning strategies were also highlighted. Conclusions This scoping review provides a comprehensive overview of personalised learning approaches in health sciences higher education. While the findings suggest potential benefits of personalised learning, they also reveal a need for more rigorous research to evaluate its effectiveness and long-term impact on student outcomes. Future studies should focus on standardising assessment methods, exploring the role of technology in facilitating personalised learning, and investigating the scalability of these approaches across different health science disciplines. Protocol registration link https://osf.io/nu4yj/ .